ISLAMIC LAW OF PROCEDURE: An Analysis of Kitâb al-Qâdhî ila al-Qâdhî in Islamic Legal Literature - Mhd. Syahnan; Abd. Mukhsin (Islamijah: Journal of Islamic Social Sciences, 2020)
Abstrak: Hukum Acara Islam: Analisis Kitâb al-Qâdhî ila al-Qâdhî dalam Literatur Hukum Islam. Telah jamak diterima di sementara kalangan ilmuwan bahwa hukum Islam tidak memiliki prosedur, dan memiliki jejak akar kemunculannya pada sistem yang dikenal dalam sistem hukum sekuler. Esai ini menganalisis asal usul gagasan prosedur hukum dengan menelusuri konsep awal yang ditemukan dalam genre Kitâb al-Qâdhî ilâ al-Qâdhî yang tergabung dalam literatur hukum fuqaha' atau ahli hukum Islam. Penelitian ini adalah penelitian kualitatif dengan menganalisis materi hukum pada surat hakim kepada hakim lain yang ditemukan dalam karya-karya berbagai ulama hukum Islam. Temuan penelitian ini mengimplikasikan bahwa meskipun ada penyederhanaan beberapa ilmuwan pada hukum pembuktian Islam, ada diskusi yang sangat kompleks tentang masalah ini dalam karya ulama hukum Islam. Selanjutnya, catatan sejarah hukum pembuktian dalam Islam ini telah menjadi bagian integral dari praktik sosial dan hukum pada masa awal, yang sejarahnya dapat dianggap sebagai konsepsi awal hukum pembuktian dalam Islam.Kata Kunci: Hukum Islam, prosedur, bukti, dokumenter, sejarah hukumAbstract: It has been commonly accepted amongst some scholars that Islamic law lacks of procedure and that it had indebted greatly to the system known in the secular system of law. This essay attempts to analyze the origin of the idea of the law procedure by tracing the very early concept found in the genre of Kitâb al-Qâdhî ilâ al-Qâdhî (a letter form one judge to another judge) incorporated in the legal literature of fuqahâ’ or Islamic jurisprudents. The study is a qualitative research by in depth analysis on legal materials on the letter of a judge to another judge found in the works of various Islamic law scholars. The finding of this study implies that despite the over-simplication of some scholars on the Islamic law of evidence, there exist a very complex discussion of the issue in the works of Islamic law scholars. It is conceivable to assert that this historical record of law of evidence in Islam had become an integral part of the social and legal practices of the early time that could be regarded as the early inception of law of evidence in Islam. Keywords: Islamic law, procedure, evidence, documentary, legal history